The importance of the modern methods of metrological control of products - Voropaiev, Myroslav (National Technical University "Kharkiv Polytechnic Institute", 2025)
Metrological control plays a critically important role in ensuring the quality and safety of products, technical equipment and services [1]. In the context of rapid human-centered progress, the implementation of modern methods and means of metrological control is becoming a necessity for the stable functioning of the economy and society as a whole [2].
Keywords: metrological control; economic stability; human well-being; measurement accuracy; sustainable development